2016
DOI: 10.1186/s13075-016-0949-6
|View full text |Cite
|
Sign up to set email alerts
|

IL-23/Th17 axis is not influenced by TNF-blocking agents in ankylosing spondylitis patients

Abstract: BackgroundAdvances in pathophysiology and treatment of ankylosing spondylitis (AS) was recently demonstrated. However, the effect of anti-TNF in the newly described inflammatory pathways involved pathogenesis of this disease remains to be determined. The aim of our study was, therefore, to investigate long-term influence of anti-TNF drugs in IL-23/IL-17 axis of AS patients and their possible correlation with treatment, clinical, laboratory and radiographic parameters.MethodsEighty-six AS anti-TNF naïve patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 50 publications
3
24
0
2
Order By: Relevance
“…However, we found no direct correlation between Th17 cell frequencies and disease activity as defined by the BASDAI score. A lack of correlation has been previously reported by some research groups [11,15,52]. In contrast, other researchers found a correlation between BASDAI scores and Th17 cell frequencies or IL-17 levels in the serum [13,18].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, we found no direct correlation between Th17 cell frequencies and disease activity as defined by the BASDAI score. A lack of correlation has been previously reported by some research groups [11,15,52]. In contrast, other researchers found a correlation between BASDAI scores and Th17 cell frequencies or IL-17 levels in the serum [13,18].…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, EP2 and EP4 differentially regulate IL-17A and IL-17F secretion by Th17 cells [51]. Interestingly, PGE 2 levels are increased in the peripheral blood of patients with high disease activity but not in the blood of patients with low disease activity [52]. Compared to AS, EP4 plays a less significant role in Th17 cell induction in RA (Additional file 2: Figure S2b).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, corticosteroids and TNF-α inhibitors may potentially modulate the number of Th17 cells and the levels of circulating IL-17A ( 19 ). On the contrary, a previous work has shown that the IL-23/Th17 axis is not influenced by TNF inhibitors, since after 24-month administration of these agents in patients with AS, IL-23 remained unchanged and stayed elevated while in parallel a clinical improvement was observed ( 20 ). In addition, in the study by Hayashi et al ( 11 ), 15 of 30 patients with AS received a TNF inhibitor, but MAIT cell frequency or IL-17A production by MAIT cells did not differ between patients who received the biological agent and those who did not.…”
Section: Discussionmentioning
confidence: 86%
“…Anti-TNF therapy was associated with increased expression levels of miR-7114-5p. Milanez et al found that the use of anti-TNF therapy in patients with AS did not affect the plasma level of IL-23 [ 28 ]. The use of anti-TNF therapy might indicate that these patients with AS had more severe or more active disease.…”
Section: Discussionmentioning
confidence: 99%